Efektivitas Pembelajaran Bahasa Arab Berbasis Aplikasi Mondly Arabic Terhadap Maharah Istima’ Siswa Madrasah Aliyah - Acmad Komarudin; Syarifuddin; Miftachul Taubah (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the effectiveness of the Mondly Arabic application in improving the listening skills (maharah istima’) of eleventh-grade students at MA Miftahul Falah Capang Purwodadi Pasuruan. This study used a quantitative approach with an experimental type through a one-group pretest–posttest design. The research subjects were 13 students selected using a saturated sampling technique. Data were collected through pretest and posttest tests to measure students' listening skills before and after the application of the Mondly Arabic application. Data analysis was carried out in stages, starting with descriptive analysis to determine the average value and improvement in students' listening skill scores. Next, a normality test was conducted as a prerequisite test for inferential analysis. Hypothesis testing was carried out using a paired sample t-test to determine significant differences between the pretest and posttest results. The results showed that the average pretest score of 66.92 increased to 77.69 in the posttest, and the difference was proven to be statistically significant. These findings indicate that the Mondly Arabic application is effective as a digital-based Arabic language learning medium, especially in improving listening skills through the presentation of authentic audio and interactive exercises. This research provides an empirical contribution to the development of Arabic language learning strategies in Madrasah Aliyah that utilize digital technology optimally.